ByzRev 07.2025.006: Theodore Metochites, On Morals or Concerning Education. Translated by Sophia Xenophontos: (Dumbarton Oaks Medieval Library 61). Cambridge, Massachusetts – London: Harvard University Press 2020. - Kaltsogianni, Eleni (The Byzantine Review, 2025)
Theodore Metochites, On Morals or Concerning Education. Translated by Sophia Xenophontos (Dumbarton Oaks Medieval Library 61). Cambridge, Massachusetts – London: Harvard University Press 2020. xxvi, 285 pp. – ISBN 978-0-6742-4463-4